Doing social innovation: a guide for practitioners : this report was written as part of the TEPSIE project, a research project funded by the European Union under the 7th Framework Programme and is an acronym for “The theoretical, rmpirical and policy foundations for building social innovation in Europe” - Simon, Julie; Schimpf, Gudrun-Christine (European Commission, DG Research, 2014)
This website contains a searchable database of information on social innovation, accessable by a search engine and by map and by the browsing keywords.
Gesehen am 10.02.2020